2021
DOI: 10.33448/rsd-v10i4.14321
|View full text |Cite
|
Sign up to set email alerts
|

Ligantes asfálticos modificados: Uma análise bibliográfica

Abstract: A aplicação de ligantes asfálticos modificados em pavimentos rodoviários vem crescendo de forma sólida nas últimas décadas. Esse fato justifica-se por motivos diversos como o advento do grande avanço das indústrias químicas, a consagração da utilização de materiais poliméricos em obras de reforços e diversas vantagens que surgem desses fatos como economia, segurança, durabilidade, dentre outros. Nessa temática, o presente trabalho tem por objetivo fazer uma revisão bibliográfica abordando as principais pesquis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In order to reduce the viscosity of the asphalt and improve its workability, various additives such as recycled vegetable oils and engine oil have been suggested [ 9 , 12 , 20 , 21 ]. A study carried out by Pereira et al [ 25 ] revealed that in recent years, there has been also greater interest in the application of vegetable oils as modifiers for asphalt binders. Haghshenas et al [ 8 ] evaluated the effects of aromatic extracts, paraffinic oil, naphthenic oil, triglycerides/fatty acids, and tall oil on the resistance to cracking associated with aging and the resistance to moisture damage of modified asphalt binders.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the viscosity of the asphalt and improve its workability, various additives such as recycled vegetable oils and engine oil have been suggested [ 9 , 12 , 20 , 21 ]. A study carried out by Pereira et al [ 25 ] revealed that in recent years, there has been also greater interest in the application of vegetable oils as modifiers for asphalt binders. Haghshenas et al [ 8 ] evaluated the effects of aromatic extracts, paraffinic oil, naphthenic oil, triglycerides/fatty acids, and tall oil on the resistance to cracking associated with aging and the resistance to moisture damage of modified asphalt binders.…”
Section: Introductionmentioning
confidence: 99%